PENERAPAN MODEL PEMBELAJARAN KOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) UNTUK PENINGKATKAN BELAJAR SISWA - ANJAR SARI, RESTI (PGSD FIP UNESA, 2015)
Abstrak Adanya aktivitas guru yang tetap dalam pengajaran, aktivitas siswa yang cenderung bersikap acuh,diam tidak aktif dan sesekali menguap serta hasil belajar yang kurang memuaskan itu semua terlihat di beberapa kelas di SDN Sumolawang Mojokerto. Hal inilah yang mendorong peneliti untuk melaksanakan  suatu Penelitian Tindakan Kelas. Penelitian Tindakan kelas bertujuan untuk meningkatkan aktivitas guru  dan siswa agar lebih aktif dinamis serta yang lebih penting untuk meningkatkan hasil belajar siswa dan meningkatkan mutu pendidikan di SDN Sumolawang Mojokerto. Untuk itu diperlukanlah suatu model pembelajaran sebagai solusi untuk mengatasi permasalahan tersebut maka dipilihlah Pembelajaran Kooperatif Tipe STAD. Pada Pembelajaran Kooperatif tipe STAD ini siswa dibagi menjadi beberapa kelompok,yang masing – masing kelompok beranggotakan 4 – 5 orang. Pada pembelajaran ini siswa dalam kelompok – kelompok tersebut dibimbing dan diarahkan guru untuk berdiskusi dan mengutarakan pendapat secara terbuka serta mempresentasikan hasil diskusinya ke depan kelas. Di samping itu guru juga memberikan kuis bagi siswa. Guru akan memberikan penghargaan pada siswa dan kelompok yang berprestasi dalam pembelajaran itu. Pada pembelajaran  kooperatif ini ada intensitas komunikasi yang intensif antara guru dengan siswa dan antara siswa dengan siswa. Hasil dari Penelitian Tindakan Kelas ini dapat terlihat setelah melalui tiga (3) siklus pembelajaran, hal ini terbukti dengan adanya peningkatan indikator pada aktivitas guru,siswa dan hasil belajar siswa dari perbandingan data temuan awal, siklus I sampai siklus III. Kata  Kunci  :  Pembelajaran  kooperatif  STAD, Pembelajaran  Tematik, Hasil  Belajar   Abstract There are some problems in Social subject teaching in Sumolawang Elementary School Mojokerto such as unchanged teaching manner from day to day,so the student  become bored,tend to sleep, the students are not active,they are not involved enough in the way answer the questions in Social Subject. And the last problem is the end score teaching result is not satisfied, most of them gets under limited score of success category. Due to  these problems,there must be problem solving, one of  problem solving is through teaching manner changed. Class action research is needed to try teaching action manner change, of course in this research using cooperative learning model,in STAD (Students Teaching Achievement Divisions) type. This Class Action Research is doing  in three sessions. Through this research hopefully to increase activities of teacher and students,also student score learning result,  and especially to increase the quality of learning in Sumolawang Elementary School. In Cooperative learning STAD type, students are divided into several groups, each groups are consist of 4 until 5 members. In this learning manner the teacher should prepare the material of teaching seriously. She / He must guide each groups in discussion and presenting the result. The open discussion is  use in this model and the students presents his / her ideas in front of the class. Beside this teacher gives the student quiz / questions. The teacher gives award for the best performance students,in groups or individually. There are intensive communication between teacher with student and student with student. The condition of teaching process become comfortable and the students are happy. The result of this research is shown after three session, the proof is shown through the data, there are increasing teacher  and student activities, from based data, session I until III and the most important thing is the poin or score of student learning result increase from session I until session III, moreover the result is satisfied, its more students get score than the limited score which is determined success category  (  80% and ≥ 70). Key  Word  :  Cooperative  Lerning  Type  STAD, Tematic  Learning, student’s  Score